Somatic embryogenesis and genetic transformation in plants - Aslam, Junaid; Sharma, M. P.; Srivastava, P. S. [ (Prem S.)] (Narosa Publishing House, 2012)
SOMATIC EMBRYOGENESIS AND GENETIC TRANSFORMATION IN PLANTS discusses pivotal role of somatic embryogenesis in micropropagation, advantages of somatic embryogenesis over organogenesis, effect of external and internal factors associated with the embryogenic cell growth and developmental process, embryo encapsulation and in vitro selection; somatic embryogenesis in ornamentals, fruit yielding and medicinally valuable plants, production of phytochemicals by embryogenic cultures; histomorphological studies of embryogenic callus to identify different stages of somatic embryos and Agrobacterium-mediated genetic transformation and plantlet regeneration via somatic embryogenesis in food, fruit, fiber and medicinally important plants.